The Patient Centered Assessment Method (PCAM): Integrating the Social Dimensions of Health into Primary Care. Issue 1 (2015) - Pratt, Rebekah; Hibberd, Carina; Cameron, Isobel M.; Maxwell, Margaret
Background: Social dimensions of health are known to contribute to what is often termed "patient complexity, " which is particularly common among patients with multimorbidity. Health-care professionals require tools to help them identify and manage these aspects of patient needs. Objectives: To examine: (i) the Patient Centered Assessment Method (PCAM), a tool for assessing patient complexity in ways that are sensitive to the biopsychosocial dimensions of health, in primary care settings in Scotland; (ii) the impact of the PCAM on referral patterns and its perceived value; and (iii) the PCAM's perceived applicability for use in a complex patient population. Design: Two studies are described: (i) a mixed-methods prospective cohort study of the implementation of the PCAM in primary care clinics; and (ii) a qualitative exploratory study that evaluated the value of the PCAM in a complex patient population. Results: Use of the PCAM did not impact patient satisfaction or perception of practitioners' empathy, but it did increase both the number of onward referrals per referred patient (9–12%) and the proportion of referrals to non-medical services addressing psychological, social, and lifestyle needs. Nurses valued the PCAM, particularly its ability to help them address psychological and social domains of patients' lives, and found it to be highly relevant for use in populations with known high complexity. Conclusions: The PCAM represents a feasible approach for assessing patient needs with consideration to the social dimensions of health, and allows practitioners to refer patients to a broader range of services to address patient complexity.